Preparation method of carbon-ceramic brake disc and carbon-ceramic brake disc

By using a mixture of boron nitride, ethanol and silicon particles to perform the melt-silicon seepage process of carbon ceramic brake discs, the problem of adhesion of residual silicon material and carbon ceramic brake discs after silicon seepage is solved, and product quality and production efficiency are improved.

CN119707532AActive Publication Date: 2025-03-28JIANGYOU TIANQI ZHIHE TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411709961.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-28
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

During the silicon seepage process, existing carbon ceramic brake discs are prone to cause residual silicon material to stick to carbon ceramic brake discs, increasing the difficulty of cleaning and affecting product quality and production efficiency.

Method used

The mixture consisting of boron nitride, ethanol and silicon particles is used to melt the silicon seepage, and the residual silicon material is isolated through the boron nitride layer to avoid adhesion with the carbon ceramic brake disc, and a microporous structure is formed through the evaporation of ethanol to improve the oozing efficiency of the silicon material.

Benefits of technology

It effectively avoids the adhesion between residual silicon material and carbon ceramic brake disc after silicon seepage, reduces the subsequent cleaning process, reduces the risk of material shortage/feeding, and improves the production efficiency and surface structural integrity of carbon ceramic brake discs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005155424970000041
    Figure BDA0005155424970000041
  • Figure BDA0005155424970000051
    Figure BDA0005155424970000051
  • Figure BDA0005155424970000061
    Figure BDA0005155424970000061
Patent Text Reader

Abstract

The invention relates to the technical field of brake discs, and particularly discloses a preparation method of a carbon-ceramic brake disc and the carbon-ceramic brake disc. The preparation method of the carbon-ceramic brake disc provided by the invention comprises the following steps: preparing a mixture: weighing the following components in parts by weight: 10-20 parts of boron nitride, 15-20 parts of 75-100% ethanol and 60-75 parts of silicon particles, uniformly mixing the components, and drying to obtain the mixture; the mixture is placed at the bottom of a crucible, then a C / C prefabricated body is placed on the mixture, the crucible is placed in a high-temperature furnace to be subjected to melt siliconizing, and the carbon ceramic brake disc is obtained through cooling. The preparation method of the carbon-ceramic brake pad provided by the invention has the advantages of high production efficiency, good surface structure integrity of the obtained carbon-ceramic brake pad and the like, and has a very good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of brake discs, and in particular to a method for preparing a carbon-ceramic brake disc and a carbon-ceramic brake disc. Background Art

[0002] With the rapid development of modern automobile technology industry, automobile sports performance is getting higher and higher, and higher requirements are also put forward for automobile braking performance. In order to meet these requirements, brake materials need to have the characteristics of lightweight, high temperature oxidation resistance, corrosion resistance and high temperature thermal decay resistance. Carbon-ceramic composite materials are regarded as one of the ideal materials for the next generation of automobile brake discs due to their excellent friction performance, low density (about one-third of the commonly used cast iron materials), excellent corrosion resistance and thermal decay friction performance.

[0003] In the production process of carbon-ceramic brake discs, the common siliconizing process mainly includes the liquid phase infiltration (LSI) process. The existing LSI process usually places a C / C preform pad under the brake disc as a support and silicon absorption channel, and then adds an appropriate amount of silicon powder from the inner ring of the brake disc into the crucible, and performs melt siliconization through a high-temperature furnace; however, the above process easily causes a large amount of residual silicon material to accumulate at the bottom of the carbon-ceramic brake disc after siliconizing, causing it to adhere to the carbon-ceramic brake disc. At the same time, the C / C preform pad will also adhere to the carbon-ceramic brake disc during the siliconizing process, which not only increases the difficulty of cleaning, but also easily causes material shortage or material drop during the cleaning process, affecting product quality and production efficiency. Summary of the invention

[0004] In order to solve the problem of residual silicon material and adhesion of C / C preform pads to carbon-ceramic brake discs in the existing siliconizing process, the present application provides a method for preparing a carbon-ceramic brake disc and a carbon-ceramic brake disc.

[0005] In a first aspect, the present application provides a method for preparing a carbon-ceramic brake disc, using the following technical solution: A method for preparing a carbon-ceramic brake disc comprises the following steps: Prepare a mixture: weigh the following components in parts by weight: 10-20 parts of boron nitride, 15-20 parts of 75-100% ethanol, and 60-75 parts of silicon particles, mix the components evenly, and dry them to obtain a mixture; Melt siliconization: the mixture is placed at the bottom of a crucible, and then the C / C preform is placed on the mixture, and then the crucible is placed in a high-temperature furnace for melt siliconization, and after cooling, a carbon ceramic brake disc is obtained.

[0006] The present application provides a method for preparing a carbon-ceramic brake disc. The preparation method uses a specific mixture for melt siliconization, which effectively solves the problem of residual silicon material adhering to the carbon-ceramic brake disc after siliconization in the traditional melt siliconization method, thereby improving the quality and production efficiency of the carbon-ceramic brake disc. Specifically, the present application pre-places a mixture composed of boron nitride, ethanol and silicon particles at the bottom of the crucible, and uses it as a support layer for the C / C preform. During the melt siliconization process, the silicon particles in the mixture will gradually penetrate into the C / C preform, and a boron nitride layer will gradually form on the surface of the mixture. Boron nitride has good high-temperature stability and chemical corrosion resistance. Therefore, the boron nitride layer will block the residual silicon material from the brake disc, play an effective isolation role, and avoid the adhesion of residual silicon to the carbon-ceramic brake disc. The volatilization of ethanol during the drying process can form a uniformly distributed microporous structure, which helps to improve the seepage efficiency of the silicon material and optimize the surface quality and structural integrity of the carbon-ceramic brake disc. In summary, the present application can significantly improve the production efficiency of carbon-ceramic brake discs and greatly improve the quality of carbon-ceramic brake discs by using a specific mixture for melt siliconization.

[0007] In the present application, when the amount of boron nitride is too small, silicon nodules and sticky materials will exist on the surface of the obtained carbon ceramic brake disc. When the amount of boron nitride is too large, the siliconization of the carbon ceramic brake disc will be unsaturated and the overall performance will deteriorate. When the amount of ethanol is too small, the uniformity of the mixture is poor, resulting in uneven penetration of silicon particles during the molten siliconization process, affecting the siliconization quality of the carbon ceramic brake disc. When the amount of ethanol is too large, the mixture is not easy to dry, resulting in poor encapsulation of silicon particles by boron nitride, affecting the siliconization quality of the carbon ceramic brake disc. Therefore, the present application found through experimental research that when the addition amount of each component in the mixture is controlled within the above range, the siliconization quality of the brake disc is good, and the quality of the obtained carbon ceramic brake disc is good.

[0008] In some embodiments, the weight portion of the boron nitride may be 10-15 parts or 15-20 parts.

[0009] In a specific embodiment, the weight portion of the boron nitride may be 10 parts, 15 parts or 20 parts.

[0010] In a specific embodiment, the weight parts of ethanol can be 15 parts or 20 parts.

[0011] In some embodiments, the weight proportion of the silicon particles may be 60-65 parts, 60-70 parts, 60-75 parts, 65-70 parts, 65-75 parts, or 70-75 parts.

[0012] In a specific embodiment, the weight proportion of the silicon particles may be 60 parts, 65 parts, 70 parts or 75 parts.

[0013] Optionally, the drying temperature is 75-85°C and the drying time is 30±5min.

[0014] Optionally, the melt siliconizing is carried out according to the following procedure: The first heating stage: heating to 1400-1450°C at a heating rate of 4-5°C / min, and keeping warm; The second heating stage: heating to 1650-1700℃ at a heating rate of 2-3℃ / min and keeping warm.

[0015] Optionally, the insulation time of the first heating stage is 60-80 minutes, and the insulation time of the second heating stage is 120-150 minutes.

[0016] Optionally, during the molten siliconizing process, the vacuum degree in the furnace is always maintained in the range of 200 to 300 Pa.

[0017] Optionally, the purity of the silicon particles is ≥99.9% and the particle size is 1-3 mm; the density of the C / C preform is 1.1-1.5 g / cm 3 .

[0018] Optionally, the cooling is performed according to the following procedure: The first cooling stage: keep the cooling rate no more than 2℃ / min and cool to 1000℃; The second cooling stage: nitrogen is filled into the high-temperature furnace to maintain the pressure in the furnace at 95-100KPa until it drops to room temperature and then the furnace is opened to obtain a carbon ceramic brake disc.

[0019] In a second aspect, the present application provides a carbon-ceramic brake disc, which is manufactured using the aforementioned method for preparing a carbon-ceramic brake disc.

[0020] In the present application, the carbon ceramic brake disc prepared by the preparation method of the carbon ceramic brake disc has no sticky material and no adhesion at the bottom of the brake disc after melt siliconization, and the surface is silvery and bright without color difference.

[0021] In summary, this application has the following beneficial effects: In the present application, a mixture consisting of boron nitride, ethanol and silicon particles is used to melt-siliconize a C / C preform, which can effectively avoid the adhesion of residual silicon material to the carbon-ceramic brake disc after siliconizing, reduce the subsequent cleaning process, and reduce the risk of material shortage / dropping during cleaning, thereby greatly improving the production efficiency and surface structure integrity of the carbon-ceramic brake disc. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is a schematic diagram of the structure before melt siliconization; 1-mixed material; 2-C / C preform; 3-crucible; Figure 2It is a schematic diagram of the structure after melt siliconization; 4-residual silicon and boron nitride; 5-boron nitride layer; 6-carbon ceramic brake disc; Figure 3 is a bottom photo of the carbon ceramic brake pad obtained in Example 2; Figure 4 This is a bottom photo of the carbon-ceramic brake pad obtained in Comparative Example 3. DETAILED DESCRIPTION

[0023] The present application provides a method for preparing a carbon-ceramic brake disc, comprising the following steps: (1) Preparing a mixture: Weigh the following components in parts by weight: 10-20 parts of boron nitride, 15-20 parts of 75-100% ethanol, and 60-75 parts of silicon particles, mix the components evenly, and dry them at 75-85° C. for 30±5 min to obtain a mixture; (2) Melt siliconization: The mixture is placed at the bottom of a crucible and scraped flat; then the C / C preform is placed on the mixture and lightly compacted to ensure that the plate surface is in full contact with the mixture; the crucible is placed in a high-temperature furnace, the high-temperature furnace is evacuated to the ultimate vacuum, and then melt siliconization is performed according to the following procedure: The first heating stage: heating to 1400-1450℃ at a heating rate of 4-5℃ / min, and keeping at the above temperature for 60-80min; The second heating stage: heating to 1650-1700℃ at a heating rate of 2-3℃ / min, and keeping at the above temperature for 120-150min; The vacuum degree in the furnace is maintained at 200-300 Pa during the entire heating / insulation process; (3) Cooling: After the heat preservation is completed, the temperature is cooled according to the following procedures: The first cooling stage: keep the cooling rate no more than 2℃ / min and cool to 1000℃; The second cooling stage: nitrogen is filled into the high-temperature furnace to maintain a slight positive pressure (95-100 KPa, which is maintained by supplementing nitrogen during the cooling process) until the temperature drops to room temperature and then the furnace is opened to obtain a carbon ceramic brake disc.

[0024] In the present application, the C / C preform is a porous material containing carbon fibers and deposited carbon formed by high temperature deposition after carbon fibers are needled, and the density is 0.4-0.6 g / cm 3 ; The chemical composition of boron nitride is 43.6% boron + 56.4% nitrogen, and the density is 2.26g / cm 3 , melting point 3000°C; purity of silicon particles ≥99.9%, particle size 1-3mm; crucible is graphite crucible; raw materials, reagents, solvents, etc. used in this application can be obtained commercially.

[0025] The present application is further described in detail below in combination with preparation examples, embodiments, performance testing experiments and accompanying drawings.

[0026] Preparation Example 1-7 Preparation Examples 1-7 each provide a mixed material.

[0027] The difference between the above preparation examples is that the addition amount of each component in the mixture is shown in Table 1 below.

[0028] The preparation method of the mixed material provided in Preparation Examples 1-7 is as follows: weigh each component according to the weight parts shown in Table 1, mix the components evenly, and dry them at 80° C. for 30 minutes to obtain a mixed material.

[0029] Comparative Preparation Examples 1-4 Comparative Preparation Examples 1-4 each provide a mixed material.

[0030] The difference between the above preparation example and preparation example 2 is that the addition amount of each component in the mixture is shown in Table 1 below.

[0031] Table 1 Addition amount of each component in the mixed material provided by Preparation Examples 1-7 and Comparative Preparation Examples 1-4 Examples 1-7 Examples 1-7 respectively provide a method for preparing a carbon-ceramic brake disc.

[0032] The difference between the above embodiments is that the mixed materials used in the carbon ceramic preparation method are respectively derived from Preparation Examples 1-7.

[0033] The method for preparing the carbon ceramic brake disc provided in Examples 1-7 comprises the following steps: (1) Preparation of mixed material: proceed according to Preparation Example 1-7.

[0034] (2) Melt siliconization: The mixture is placed at the bottom of a crucible and scraped flat; then the C / C preform is placed on the mixture and lightly compacted to ensure that the plate surface is in full contact with the mixture; the crucible is placed in a high-temperature furnace, the high-temperature furnace is evacuated to the ultimate vacuum, and then melt siliconization is performed according to the following procedure: The first heating stage: heating to 1400℃ at a heating rate of 4℃ / min and keeping at the above temperature for 60min; The second heating stage: the temperature is raised to 1700°C at a heating rate of 2.5°C / min, and kept at the above temperature for 120-150 minutes; the vacuum degree in the furnace is maintained at 250Pa during the entire heating / keeping process.

[0035] (3) Cooling: After the heat preservation is completed, the temperature is cooled according to the following procedures: The first cooling stage: maintain the cooling rate at 1.5℃ / min and cool to 1000℃; The second cooling stage: nitrogen is filled into the high-temperature furnace to maintain a slight positive pressure (100KPa, which is maintained by supplementing nitrogen during the cooling process) until the temperature drops to room temperature and then the furnace is opened to obtain a carbon ceramic brake disc.

[0036] Comparative Examples 1-4 Comparative Examples 1-4 respectively provide a method for preparing a carbon-ceramic brake disc.

[0037] The difference between the comparative example and Example 2 is that the mixed materials used in the carbon ceramic preparation method are derived from comparative preparation examples 1-4 respectively.

[0038] Comparative Example 5 Comparative Example 5 provides a method for preparing a carbon-ceramic brake disc.

[0039] The difference between the comparative example and Example 2 is that the mixed material is replaced by silicon particles.

[0040] Performance testing Carbon ceramic brake discs were prepared according to the methods provided in Examples 1-7 and Comparative Examples 1-5, and then the presence of silicon nodules and sticking materials at the bottom of the brake discs was observed. Various performance tests were performed on the carbon ceramic brake discs, and the results are shown in Table 2 below.

[0041] (1) Opening rate: Tested in accordance with the provisions of GB / T 1966-2024; (2) Bending strength: Tested in accordance with the provisions of GB / T 6569-2006; (3) Tensile strength: Tested in accordance with the requirements of GB / T 33501-2017.

[0042] Table 2 Performance test results of carbon ceramic brake discs obtained in Examples 1-7 and Comparative Examples 1-5 According to the test results in Table 2, the carbon-ceramic brake discs obtained in Examples 1-7 of the present application have no silicon nodules and no sticking materials on their surfaces; while the carbon-ceramic brake discs obtained in Comparative Examples 1 and 3-5 have a small or large amount of silicon nodules and sticking materials; and the carbon-ceramic brake discs obtained in Comparative Examples 3-4 have a bending strength of only 125-142 MPa, and a tensile strength of only 71-74 MPa; the carbon-ceramic brake disc obtained in Comparative Example 2 has an apparent porosity of up to 15%, a bending strength of only 109 MPa, and a tensile strength of only 67 MPa. Therefore, it is explained that the present application uses boron nitride, ethanol and silicon particles as a mixture to melt siliconize the C / C preform, and the weight proportions of the three are controlled within the following range: 10-20 parts of boron nitride, 15-20 parts of 75%-100% ethanol, and 60-75 parts of silicon particles. Under the premise of ensuring the basic performance of the carbon-ceramic brake disc, it is possible to effectively prevent the residual silicon material after siliconization from adhering to the carbon-ceramic brake disc, so that no silicon nodules remain on the surface of the brake disc, reduce the subsequent cleaning process, and reduce the risk of material shortage / dropping during cleaning, thereby greatly improving the production efficiency and surface structural integrity of the carbon-ceramic brake disc.

[0043] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made thereto based on the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.

Claims

1. A method for preparing a carbon ceramic brake disc, characterized in that: The following steps are involved: Prepare a mixture: weigh the following components in parts by weight: 10-20 parts of boron nitride, 15-20 parts of 75-100% ethanol, and 60-75 parts of silicon particles, mix the components evenly, and dry them to obtain a mixture; Melt siliconization: the mixture is placed at the bottom of a crucible, and then the C / C preform is placed on the mixture, and then the crucible is placed in a high-temperature furnace for melt siliconization, and after cooling, a carbon ceramic brake disc is obtained.

2. The method for preparing a carbon ceramic brake disc according to claim 1, characterized in that: The drying temperature is 75-85°C and the drying time is 30±5min.

3. The method for preparing a carbon ceramic brake disc according to claim 1, characterized in that: The melt siliconizing is carried out according to the following procedure: The first heating stage: heating to 1400~1450℃ at a heating rate of 4~5℃ / min, and keeping warm; The second heating stage: heat up to 1650~1700℃ at a heating rate of 2-3℃ / min and keep warm.

4. The method for preparing a carbon ceramic brake disc according to claim 3, characterized in that: The insulation time of the first heating stage is 60-80 minutes, and the insulation time of the second heating stage is 120-150 minutes.

5. The method for preparing a carbon ceramic brake disc according to claim 1, characterized in that: During the molten siliconizing process, the vacuum degree in the furnace is always maintained in the range of 200-300 Pa.

6. The method for preparing a carbon ceramic brake disc according to claim 1, characterized in that: The purity of the silicon particles is ≥99.9% and the particle size is 1-3 mm; the density of the C / C preform is 1.1-1.5 g / cm 3 .

7. The method for preparing a carbon ceramic brake disc according to any one of claims 1 to 6, characterized in that: The cooling is carried out according to the following procedure: The first cooling stage: keep the cooling rate no more than 2℃ / min and cool to 1000℃; The second cooling stage: nitrogen is filled into the high-temperature furnace to maintain the pressure in the furnace at 95-100KPa until it drops to room temperature and then the furnace is opened to obtain a carbon ceramic brake disc.

8. A carbon ceramic brake disc, characterized in that: The carbon ceramic brake disc is prepared by the preparation method of any one of claims 1 to 7.

Citation Information

Patent Citations

  • Method of making molten silicon infiltration reaction products and products made thereby

    US4120731A

  • Processes for making a silicon carbide composition

    US6398991B1

  • Porous body infiltrating method

    US6403158B1

  • Method for fusion infiltration of porous bodies

    WO2000007957A2